If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying W + -12 = -4 Reorder the terms: -12 + W = -4 Solving -12 + W = -4 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + W = -4 + 12 Combine like terms: -12 + 12 = 0 0 + W = -4 + 12 W = -4 + 12 Combine like terms: -4 + 12 = 8 W = 8 Simplifying W = 8
| 5x(2x-1)(5x+7)=0 | | b-6=-3 | | 5n(n+2)=10 | | 8(4-2x)=12-16x | | 2(2x-3)-5(1x+1)=x-4 | | a(a-9)(a-8)=0 | | 6(2q-1)=2q+8q | | N+3.4=5.6 | | n/5+3-10=30 | | a(bx-2)=cx+6 | | 6(4.5y)-12=9 | | (a+9)(a+2)=0 | | p+0.06p=148.4 | | n*5+3-10=30 | | 5x-5=4x+7 | | 15-2x-2=10x+3x+2 | | 4-5x=2(7x-3) | | -8-5n=4m | | 2(-1)+5+3x-3=5x+9 | | 8=-5+x | | 2r+4=2r-5 | | 10D+40=10 | | 25=7+3k-17 | | 13-4x+2=3x-7x+2 | | 2p+3p= | | 1+(-40+5x)=2+-1(x+5) | | 8=-5+8 | | -4.4-1.21z= | | 5x-12+15x-7+9-2x=-15 | | 12-7x-10=x-8x+2 | | t^2-2=0 | | 3a+4(2a-17)=-13 |